Determinants of foreign direct investment and its impact on economic development in Southern Africa customs Union countries - Suleiman, Najat Nassor (2013)
Foreign direct investment (FDI) has been widely acknowledged as a crucial factor for the economic growth and development of many countries. Sholars and policymakers believe that FDI can stimulate a country's economic development. Since most African countries face shortages in their domestic savings, such countries depend largely on FDI to fill the saving gap by allowing investments for various development projects. The spillover effects of FDI in the form of technology transfer and increase in the efficiency of domestic production lead to higher production and creation of more employment. Hence, FDI inflow and its impact on economic development has become an important issue to many developing nations. However, there are very few studies pertaining to the African countries or to the economic block to which they belong. Therefore, the study intends to fill the gap by examining the determinants of FDI inflow and its impact on South African Customs Union (SACU) countries’ economic development. SACU consists of five countries namely: Botswana, Lesotho, Swaziland, Namibia and South Africa. To achieve the objectives of this study, Dynamic Ordinary Least Square (DOLS) estimations were used on data covering the period from 1990 to 2010 for the FDI model and 1980 to 2010 for the growth model. The findings reveals that natural resources (LNAT), trade openness (LTRD), gross capital formation (LGCF) and infrastructure (LINFR) are positive and significant determinants of FDI for the SACU countries. The results show that a one percent increase in natural resource (LNAT), trade openness (LTRD), gross capital formation (LGCF) and infrastructure (LINFR) resulted in approximately 1.396%, 0.939%, 0.565% and 1.673% increase, respectively, in FDI inflow in SACU countries. On the other hand, economic stability is significantly but negatively related to FDI inflow into SACU countries. In addition, labor costs and market size (LMARK) are found to be an insignificant determinant of FDI inflow to SACU countries. Thus, it can be concluded that the availability of natural resources, trade openness, gross capital formation, good infrastructure and economic stability are significant factors in stimulating the FDI inflow into SACU countries. With regard to the second model, there is a satisfactory evidence to show that there is a positive impact of FDI on the economic development of the SACU countries. A one percent increase in FDI will lead to an increase in economic growth by 0.0846 percent. This result suggests that FDI exerts significant impact on the economic development of the SACU countries. Moreover, the inflow of foreign capital into SACU countries is largely resource-seeking FDI as some of the SACU countries are endowed with natural resources such as oil and minerals. Therefore, the government or policy makers should introduce more incentives and policy reforms to attract more FDI into SACU countries, especially those related to the management of natural resources. In addition, more trade agreements should be undertaken by developed nations to enhance FDI inflow which can eventually promote greater economic development of the recipient SACU countries.